Inheritance of resistance to yellow vein mosaic virus disease in interspecific crosses of Abelmoschus - KAUR, JASHANDEEP; PATHAK, MAMTA; PATHAK, DHARMINDER (The Indian Journal of Agricultural Sciences, 2021)
Okra [Abelmoschus esculentus (L.) Moench] is an important vegetable crop grown in tropical and subtropical regions of the world. The total production of okra is drastically reduced due to various biotic and abiotic stresses. Among the biotic stresses, viral disease is of major concern. In this context, the present investigation has been carried out to understand the inheritance of yellow vein mosaic virus (YVMV) disease resistance in okra using segregating populations of A. esculentus cv. Punjab Padmini × A. moschatus and A. esculentus cv. Punjab Padmini × A. tuberculatus and to study the chromosome number of the three species involved in the A. esculentus cv. Punjab Padmini, A. moschatus, A. tuberculatus and their inter-specific F1 hybrids. The results of crossability studies revealed that, the wild species A. moschatus and A. tuberculatus are compatible with cultivated specie A. esculentus cv. Punjab Padmini. Inheritance of YVMV disease has been observed to be simple and governed single dominant gene in case of A.esculentus× A. moschatus cross and a single recessive gene in A. esculentus cv. Punjab Padmini × A. tuberculatus cross.